Financial Supply Index and Financial Supply Cycles in New EU Member States - Tomislav Globan (The Vienna Institute for International Economic Studies (wiiw), 2016)
Abstract This paper introduces a new composite index – the financial supply index (FSI), which measures the level of supply of foreign capital to 11 new EU Member States (NMS). We aim to fill the gap in the literature, which has so far focused on creating indices that measure the financial conditions only, while the economic factors, also important determinants of capital flows, have been overlooked. The FSI includes both the financial and economic determinants of capital flows and is estimated using Kalman filtering, principal components and a variance-equal weights approach. Three financial supply cycles in NMS could be extracted based on the analysis of FSI dynamics. The results indicated that the main drivers of financial supply to NMS are externally determined, with economic sentiment and business climate in the eurozone carrying the highest weight. In addition, we create a new indicator – the Refinancing Risk Ratio (RRR), which relates the supply of and demand for foreign capital, to quantify the external refinancing conditions and risk faced by the government. We are able to distinguish two main episodes of high refinancing risk faced recently by the EU NMS – one during the global financial crisis, and the other during the European sovereign debt crisis, but the episodes significantly differ in nature.
Keywords: F21; F36; H63; 330; financial cycles; financial supply; new EU Member States; capital flows; refinancing conditions